Rapid Instructional Design : Learning ID Fast and Right - Piskurich, George M. (John Wiley & Sons, 2015)
The classic guide to instructional design, fully updated for the new ways we learn Rapid Instructional Design is the industry standard guide to creating effective instructional materials, providing no-nonsense practicality rather than theory-driven text. Beginning with a look at what ""instructional design"" really means, readers are guided step-by-step through the ADDIE model to explore techniques for analysis, design, development, intervention, and evaluation. This new third edition has been updated to cover new applications, technologies, and concepts, and includes many new templates, real-